Design of an Underwater Robot System for Detecting Defects in Hydraulic Structures at Hydropower Stations - ZHANG Yi; ZHU Jun; YUAN Qingqing; WENG Yewei; PENG Shidong; SHEN Weige (Kongzhi Yu Xinxi Jishu)
Current defect detection techniques for hydraulic structures at hydropower stations are conducted by inspection robots or divers, facing challenges such as limited inspection methods and the impact of water currents. In response to this, the paper developes an underwater robot system for inspection tasks based on the structural and defect characteristics of hydraulic buildings in hydropower stations. Using methodologies such as hydrodynamic simulation, and hydrostatic analysis and stability analysis, the system optimizes propulsion and layout structure, shape selection and design, solving problems inherent to body floating and caterpillar track hybrid control modes, adhesive technology for irregular dam surfaces, multi-degree of freedom attitude flipping, movement, and precise location of defects. Furthermore, independently developed post-processing software is used to consolidate data from acousto-optic-electric sensors, ensuring identification of defects, measurement, and estimation of repair material quantities, the theoretical error of software recognition is 7.4%, which is less than the 20% error rate required by the project. This solution overcomes the challenges of defect measurement and estimation of required materials for repairs. Ultimately, the objective is to facilitate autonomous underwater operations including defect inspections, locating defects, dimension measurements, and data acquisition for robots operating on flat, sloping, upright, and curved surfaces of hydraulic structures in hydropower stations. Finally, pool functional test validations have confirmed the feasibility of the proposed underwater detection robot system.